Peran Ulama Nahdlatul Ulama Dalam Mengawal Program Pemerintah Dalam Upaya Deradikalisasi di Kabupaten Karawang - Febri Rohiman Hidayat; Dadan Kurniansyah; Rachmat Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research is motivated by the existence of a deradicalization program issued by the government in tackling radicalism, which gave rise to pros and cons among the people of Karawang. NU clerics who have responsibility in fostering the ummah are required to have a role in overseeing the deradicalization program so that dangerous understandings of radicalism can be handled properly. The theory used by researchers is the characteristic role theory put forward by Horoepoetri, Arimbi and Santosa (2003) which includes five dimensional variables, namely the role of policy, the role of strategy, the role as a communication tool, the role for dispute resolution and the role in providing therapy. This study used descriptive qualitative method. Data collection techniques were carried out through triangulation which included observation, interviews and documentation studies. The data were then analyzed through three stages, namely reduction, presentation and conclusion. The results and discussion of this study show that the deradicalization policy is a wise step in tackling radicalism in Karawang, whose society is plural in religion and culture. The NU cleric's strategy in overseeing the deradicalization program is carried out collaboratively with the government but funding is still very minimal. The communication carried out by the ulama was carried out through two media, namely internet-based media and face-to-face media, then internal conflicts were found between fellow Muslims from the nahdyin and the radicals. The role of NU clerics in providing therapy for the community of former members of banned organizations is considered important because of the high negative stigma issued by the surrounding environment